Highly conductive ZrO2–x spheres as bifunctional framework stabilizers and gas evolution relievers in nickel-rich layered cathodes for lithium-ion batteries. (1st June 2022) - Kim, You Jin; Kim, Ga-Yoon; Kim, Hyun-Soo; Kim, Suji; Kim, Boran; Choi, Yoo Jung; Kim, Jaekook; Kim, Jinsoo; Ryu, Won-Hee
Abstract: The introduction of ZrO2 in a Ni-rich cathode offers a balance between its surface protection and unavoidable capacity loss due to the chemical inertness and extremely low electrical conductivity of the cathode. Here, highly conductive black ZrO2–x spheres are successfully adopted as a bifunctional framework stabilizer and gas evolution reliever for the surface of a Ni-rich cathode by tuning the band-gap energy of ZrO2 . Employing a facile reduction step, white monoclinic ZrO2 is converted into black oxygen-deficient tetragonal ZrO2–x, which significantly reduces the band-gap energy, improving the electrical conductivity. The interstitial occupancy of the black ZrO2–x spheres in the Ni-rich cathode improves the electron transport and surface structural stability via the resulting high electrical conductivity and excellent durability. The black ZrO2–x effectively suppresses the gas evolution from the Ni-rich cathode during charging at a high voltage of 4.5 V by inductively preserving the high oxidation state of Ni 2+ . These findings demonstrate that the oxygen-deficient ZrO2–x material exhibits multifunctionality to suppress gas evolution, as well as increase the capacity and protect the surface of the Ni-rich cathode. Thus, the bifunctionality of black ZrO2–x as an effective framework stabilizer and gas evolution reliever is demonstrated; it can be employed to produce Ni-rich cathodes exhibiting high capacity, long life, and high stability. Graphical abstract: " Highly Conductive ZrO2–x Spheres as Bifunctional Framework Stabilizers and Gas Evolution Relievers in Nickel-Rich Layered Cathodes for Lithium-Ion Batteries ". Image 1 Highlights: Highly conductive ZrO2-x spheres are fabricated by tunning wide band gap of ZrO2 with oxygen vacancies. Highly conductive ZrO2-x spheres are introduced as surface stabilizers and gas evolution relievers for safe and long-lasting Li-ion batteries. Conductive ZrO2-x spheres stabilize reactive Ni 3+ at surface NMC, resulting in high capacity, structural durability, low overpotentials. Gas-adsorption ability of ZrO2-x successfully relieves gas evolution on cathodes for charge at high voltage.